Between Jews and Heretics Refiguring Justin Martyr's Dialogue with Trypho - den Dulk, Matthijs (Routledge Studies in Anthropology, 2018)
Justin Martyr's Dialogue with Trypho is the oldest preserved literary dialogue between a Jew and a Christian and a key text for understanding the development of early Judaism and Christianity. In Between Jews and Heretics, Matthijs den Dulk argues that whereas scholarship has routinely cast this important text in terms of "Christianity vs. Judaism," its rhetorical aims and discursive strategies are considerably more complex, because Justin is advocating his particular form of Christianity in constant negotiation with rival forms of Christianity. The striking new interpretation　proposed in this study explains many of the Dialogue's puzzling features and sheds new light on key passages. Because the Dialogue is a critical document for the early history of Jews and Christians, this book contributes to a range of important questions, including the emergence of the notion of heresy and the "parting of the ways" between Jews and Christians.